Analysis Of The Effect Of Technology Readiness, Knowledge Sharing And Teaching Autonomy On Private School Teachers' Pedagogical Innovation - Lia, Naila Fikrina Afrih (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The specific objective of this research is to assess how technology readiness, knowledge sharing, and teaching autonomy affect the innovativeness of private school teachers the most. The study stems from the aim of enhancing the overall quality of education and the wish to always have the teaching process aligned with the latest technology. The researcher applied a quantitative explanatory method and reached the sample of 150 private school teachers through purposive sampling. For data gathering, a five-point Likert scale questionnaire was used, whereas multiple linear regression was used for data processing. The findings indicated that all three independent variables had a significant and positive influence on the pedagogical innovation dependent variable. Theoretically, this study adds value to the already existing literature on education management and learning innovation. The practical side of the research is that it gives private school management the strategic implications of facilitating pedagogy innovation through creating a technology-ready environment, promoting knowledge sharing, and providing teachers with supervision freedom as the three main components.